Rancang Bangun Sistem Informasi Monitoring Kinerja Karyawan Berbasis Web dengan Metode Balanced Scorecard pada BPJS Ketenagakerjaan - Rizky Azwar Alfandi Simare Mare; Triase Triase (Jurnal Teknologi Informasi dan Multimedia, 2024)
With rapid technological advancements, information systems have evolved significantly from mere data processing tools to integrated solutions that support decision-making and strategic management. The implementation of technologies such as cloud computing, big data analytics, and artificial intelligence has further enriched the functions and capabilities of information sys-tems. Additionally, the development of information systems includes more intuitive user inter-faces, mobility, and connectivity that allow quick and easy access to information. In the workplace, one of the problems employees face is performance evaluations that are not objective and transparent. Therefore, companies need to conduct performance appraisals that can motivate employees to achieve rewards for their work. Based on these issues, the development of an em-ployee performance monitoring and reporting information system is needed to help companies manage employee evaluations objectively and transparently. BPJS Ketenagakerjaan, as a provider of social security programs in Indonesia, offers protection against employment risks. BPJS Ketenagakerjaan Kota Medan, in particular, plays an important role in providing social protection to workers and their families, creating a safer work environment, and contributing to national economic stability. Employee performance appraisals are conducted using the Balanced Scorecard (BSC) method based on four perspectives: financial, customer, internal business process, and learning and growth. The software development follows the waterfall method, with system design modeling using Unified Modelling Language (UML). The research results in an employee per-formance monitoring and reporting information system that facilitates companies in managing reporting and performance appraisals because the system implements calculations according to the BSC evaluation method.